Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter 1 - Section 1.7 - Combinations of Functions; Composite Functions - Concept and Vocabulary Check - Page 257: 14



Work Step by Step

RECALL: (1) $(f \circ g)-f(g(x))$ (2) $(g \circ f)(x) = g(f(x))$ It often happens that $(f \circ g)(x) \ne (g \circ f)(x)$. To illustrate, have a look at the example below: Let $f(x) = x+2$ $g(x) = 2x$ $(f \circ g)(x) = f(g(x)) = 2x + 2$ $(g \circ f)(x) = g(f(x)) = 2(x+2) =2x+4$ Thus, the given statement is false.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.